Design and Analysis Comparison of Surface Acoustic Wave-Based Sensors for Fabrication Using Additive Manufacturing - ERSOY, SEZGİN (HINDAWI LTD, 2021)
Sensors have become an integral part of our everyday lives by helping us converting packets of data to make important decisions. Due to this reason, researches are done constantly to improve the fabrication processes of sensors by making them more user-friendly, less time-consuming, and more cost-effective. The application of any fabrication solution that offers those advantages will have a major impact on the manufacturing of modern sensors. To address this issue, a 3D printed Surface Acoustic Wave (SAW) temperature sensor is presented in this paper. The modelling and analysis of such a sensor have been performed for both aluminium and copper electrodes using COMSOL software. In total, 4 different sensing structures, 2 each for both aluminium and copper electrodes based one-port resonators, are designed and analysed for their application in temperature sensing. The resulting responses of those sensors are approximately 2.19 MHz and 424.01 MHz frequency ranges. The novelty lies in the possibility of mass-producing such a sensor using additive manufacturing will have a direct impact in the areas where conventional electronics cannot be utilized.
Keywords: SAW; DEVICE; LITHOGRAPHY; TEMPERATURE; ELECTRONICS; TECHNOLOGY; MEMBRANE; PRESSURE